Perancangan Sarana Layanan Akademik Dalam Mengantisipasi Penyebaran Penyakit Menular (Covid-19) Pasca Pandemik - Nunung Nuring Hayati; Dano Quinta Revana (Jurnal Rekayasa Sipil dan Lingkungan, 2022)
The Covid-19 virus, which attacks the respiratory system and is classified as an infectious disease, has been designated a global pandemic. One way to prevent the Covid-19 virus is to implement physical distancing from other people. The impact of this pandemic is affecting the learning system so that the teaching and learning process is carried out online during the pandemic. If later the teaching and learning process is carried out offline, it is necessary to prevent and anticipate the virus so that it does not spread during the teaching and learning process, such as the design of the classroom layout, the design of a virus barrier product design, and the design of a special room design for people with infectious diseases. The layout design in the classroom is made at 50% of the capacity it should have during the previous normal study, to implement physical distancing or keep a distance. Normal human circulation is 2 m2/person, in the new normal period a minimum of 4 m2/person is required. The product design is to limit oneself when the teaching and learning process takes place with the Divider product which is placed on the classroom desk. This divider is made of clear acrylic, sized according to a study table that can be easily carried, easy to store, safe, sturdy, and easy to clean. ABSTRAK Virus Covid-19 yang menyerang sistem pernapasan dan tergolong penyakit menular yang telah ditetapkan menjadi pandemi global. Salah satu pencegahan virus Covid-19 yaitu menerapkan physical distancing dengan orang lain. Dampak dari pandemi ini adalah mempengaruhi pada sistem belajar, sehingga proses belajar mengajar dilakukan secara daring selama pandemi. Jika nantinya proses belajar mengajar dilakukan secara luring, diperlukan pencegahan dan antisipasi virus agar tidak menyebar selama proses belajar mengajar, seperti perancangan tata ruang dalam kelas, perancangan desain produk pembatas virus, dan desain perancangan ruangan khusus untuk penderita penyakit menular. Perancangan tata letak pada ruang kelas dibuat 50% dari kapasitas seharusnya saat belajar normal sebelumnya, guna menerapkan physical distancing atau jaga jarak. Normal sirkulasi manusia adalah 2 m2/orang, pada masa new normal dibutuhkan minimal 4 m2/orang. Perancangan produk guna membatasi diri ketika proses belajar mengajar berlangsung dengan produk Divider yang diletakkan pada meja belajar kelas, Pembatas ini terbuat dari akrilik bening, berukuran sesuai dengan meja belajar yang dapat mudah dibawa, mudah disimpan, aman, kokoh, dan mudah untuk dibersihkan.